ASSRJ 2018
DOI: 10.14738/assrj.53.3846
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation Of Pensi (Corbicula Moltkiana) Fishing Activity In Lake Maninjau, West Sumatera Indonesia

Abstract: Pensi (Corbicula moltkiana) is the name a kind of freshwater mussel, which inhabit the Lake Maninjau, West Sumatra Province, Indonesia. Pensi has been utilized and important for the people in the Lake Maninjau region. The pensi fishing activities continuously will impact to their availability in the future. The purpose of this study is to observe the characteristics of pensi fishing activity in Lake Maninjau. The research conducted at the Maninjau Lake area, District of Tanjung Raya, Agam Regency West Sumatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…In addition, they noted that when the IWCCF owners harvest their fish, they can harvest significant numbers of ikan bada at the same time from the cages area. In addition, [37] observed that IWCCF density impacted pensi abundance; the denser IWCCF, the less its abundance is observed.…”
Section: Results Of the Interviewsmentioning
confidence: 95%
“…In addition, they noted that when the IWCCF owners harvest their fish, they can harvest significant numbers of ikan bada at the same time from the cages area. In addition, [37] observed that IWCCF density impacted pensi abundance; the denser IWCCF, the less its abundance is observed.…”
Section: Results Of the Interviewsmentioning
confidence: 95%
“…Danau Maninjau terletak di Provinsi Sumatera Barat, dan merupakan salah satu danau di Indonesia yang memiki multiguna fungsi. Danau Maninjau ini digunakan untuk pariwisata, sumber air untuk pembangkit listrik tenaga air, aktivitas perikanan, budidaya keramba, dan sebagai sumber bahan baku air minum (Lukman, 2015). Ikan nila (Oreochormis niloticus L) merupakan salah satu budi daya ikan dalam bentuk keramba jala apung (KJA).…”
Section: Pendahuluanunclassified